The Association of Subclinical Atherosclerosis with Incident Heart Failure: The Atherosclerosis Risk in Communities Study - Effoe, Valery (Wake Forest University, 2013)
Background: Atherosclerosis plays a central role in the pathophysiology of coronary heart disease (CHD), which is believed to be the most common etiology for heart failure (HF). Greater carotid intima-media thickness (IMT), a measure of subclinical atherosclerosis, is associated with left ventricular myocardial dysfunction, a subclinical marker of HF. We investigated the association of carotid IMT with incident HF among middle-aged whites and blacks, controlling for major cardiovascular disease (CVD) risk factors.
Keywords: Carotid intima-media thickness; Diabetes mellitus; Heart failure; Subclinical atherosclerosis